Subventricular zone-derived neuroblasts use vasculature as a scaffold to migrate radially to the cortex in neonatal mice - Le Magueresse, Corentin; Bark, Christine; Eliava, Marina; Khrulev, Sergey; Monyer, Hannah (Cerebral cortex, 2012)
Neurons continue to be generated in the subventricular zone (SVZ) throughout postnatal development and adulthood in rodents. Whereas in adults, virtually all neuroblasts migrate tangentially to the olfactory bulb via the rostral migratory stream (RMS), in neonates, a substantial fraction migrate radially through the corpus callosum (CC) to the cortex. Mechanisms of radial cortical migration have remained unknown. We investigated this by taking recourse to enhanced green fluorescent protein (EGFP)-labeled neuroblasts in the CC and deep cortical layers of neonatal mice and found that they are frequently located adjacent to vasculature. Using time-lapse 2-photon microscopy in acute brain slices, we demonstrate that EGFP-labeled neuroblasts migrate along blood vessels. Although in close proximity to blood vessels, migrating neuroblasts are separated from endothelial cells by 1-2 layers of astrocytic processes, as revealed by electron microscopal studies of retrovirally labeled postnatally born cells. We propose that 2 factors could contribute to the decline of radial migration to the cortex during postnatal development, namely the establishment of a glial sheath delineating the RMS and a gradual decrease in the density of blood vessels in the CC. Together, our data provide evidence for a new mode of radial cortical migration of SVZ-generated neurons involving vasculature and astrocytes.
Gesehen am 11.04.2018